1999
DOI: 10.1002/(sici)1096-9861(19991004)412:4<617::aid-cne4>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Retinal axon regeneration in peripheral nerve, tectal, and muscle grafts in adult rats

Abstract: This study examined whether prior regenerative growth through peripheral nerve (PN) bridging grafts influenced the specificity with which lesioned adult rat retinal ganglion cell (RGC) axons grew into co‐grafts of developing target tissue (fetal superior colliculus). Growth into nontarget (muscle) tissue was also examined. Autologous PN was grafted onto the transected optic nerve. After 14 days, the distal ends of the PNs were placed next to, or inserted into, embryonic tectal tissue or into autologous muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This is likely to be due to many factors, including the inhibitory environment of the CNS, scarring at the distal graft-host interface, 14 and the growth-promoting influence of the graft itself. 15 Over the past few years there has been increasing interest in using another glial cell type, the olfactory ensheathing glia (OEG) cell. 16 Under normal circumstances OEG guide new primary olfactory axons growing from the olfactory epithelium towards their targets, the olfactory bulb glomeruli, where they synapse on, for instance, the dendrites of mitral cells.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to be due to many factors, including the inhibitory environment of the CNS, scarring at the distal graft-host interface, 14 and the growth-promoting influence of the graft itself. 15 Over the past few years there has been increasing interest in using another glial cell type, the olfactory ensheathing glia (OEG) cell. 16 Under normal circumstances OEG guide new primary olfactory axons growing from the olfactory epithelium towards their targets, the olfactory bulb glomeruli, where they synapse on, for instance, the dendrites of mitral cells.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, PN grafts are used to repair defects in human PN that are too large to allow direct re‐attachment of injured stumps (Millesi, 1991; Bain, 1998). In adult central nervous system (CNS), an environment not normally conducive to axon regeneration, experimental PN autografts have been used in animals to induce axon regrowth across brain and spinal cord injury sites (Bray & Aguayo, 1989; Cheng et al ., 1996; Tan & Harvey, 1999). Preliminary human trials have also been reported (Cheng, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that injury or lesions open up axonal or synaptic space and modify the expression of neuronal growth factors, and are required for transplanted or endogenously derived neurons to project through the adult brain (Macklis, 1993;Magavi et al, 2000;Singec and Snyder, 2007). Injury and the subsequent denervation induces changes in the target regions of the projections, the expression of factors important for neuronal survival and neurite outgrowth, and the number and types of microglia and astrocytes present in the brain (reviewed by Tan and Harvey, 1999). In the current experiments, embryonic LGE or cortical neurons transplanted into the striatum projected to distant subcortical targets even in the relative absence of injury, suggesting that permissive and guidance signals are present in the intact brain.…”
Section: Discussionmentioning
confidence: 69%